(untitled) (ModaPalavra e-periódico, 2025)
With the purpose of contributing to the theoretical understanding of the relationship between Fashion and Fashion Design, this study aims to analyze the characteristics and approaches of academic-scientific productions that mention the terms "fashion" and/or "fashion design" in Brazil . The scope of the study object comprises academic-scientific productions, with the scope of the Stricto Sensu Postgraduate Programs in Design and a Stricto Sensu Postgraduate Program in Textile and Fashion. This is a descriptive study of a primarily qualitative nature. The data was collected from a mapping of the aforementioned terms present in the titles, abstracts and keywords of the productions. The period delimited for the analysis corpus is from January 2001 to May 2024. A lexicographic textual analysis was carried out with the support of the IRAMUTEQ software. The results indicate that the publications discuss themes that are sometimes close and sometimes distant. Fashion and fashion design have been investigated from the perspective of sustainability, innovation and methodological criteria, as well as in the communicational way of representing cultural identity.